El papel de los líderes religiosos de israel-palestina en el proceso de paz israelo-palestino - Fontes, Luis (UNISCI Discussion Papers, 2007)
In Israel-Palestine, as in the rest of the Middle East, religion is a fundamental factor in shaping the identity of people and it affects all aspects of social and political life. It is necessary to tackle the religious issue to achieve true pace, beyond mere short-lived arrangements. The main religious figures of Israel and Palestine are too dependent on the political power and this dependence makes them unable to play a prophetic role of reconciliation. Still, it has been a tragic mistake of both Israeli politicians and the former Palestinian National Authority to ignore religious leaders, to keep them out of the peace process. The effect has been the contrary to the pursued one: to make them suspicious of the process and to polarize both parties public opinion even more. Finally, it will be impossible to solve the thorny issue of Jerusalem’s holy sites without the active involvement of the religious establishment.